2011
DOI: 10.4061/2011/587547
|View full text |Cite
|
Sign up to set email alerts
|

The Constitutive Expression of Type X Collagen in Mesenchymal Stem Cells from Osteoarthritis Patients Is Reproduced in a Rabbit Model of Osteoarthritis

Abstract: The expression of type X collagen (COL X), a late-stage chondrocyte hypertrophy marker in human mesenchymal stem cells (MSCs) from osteoarthritis (OA) patients poses a major setback to current cartilage and intervertebral disc tissue engineering efforts. However, it is not yet clear whether COL X is expressed by all human bone marrow stem cells or if it is related to age, gender, site, disease status, or drug therapy. In the current study, we report that COL X expression is upregulated in MSCs from rabbits in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
(72 reference statements)
2
6
0
Order By: Relevance
“…In CM conditions, at seven days the pellets resemble the prechondrogenic mesenchyme tissue, evidenced by high expression of Col type I, confirming data from developmental studies reporting that it is highly expressed in early chondrogenesis [37][38][39][40][41][42]. The latter has then been further confirmed by the SOX9 expression [37], in both CM and CAG-supplemented pellets (Figure 4A-C).…”
Section: Discussionsupporting
confidence: 82%
“…In CM conditions, at seven days the pellets resemble the prechondrogenic mesenchyme tissue, evidenced by high expression of Col type I, confirming data from developmental studies reporting that it is highly expressed in early chondrogenesis [37][38][39][40][41][42]. The latter has then been further confirmed by the SOX9 expression [37], in both CM and CAG-supplemented pellets (Figure 4A-C).…”
Section: Discussionsupporting
confidence: 82%
“…In this study, anterior cruciate ligament transaction (ACLT) combined with complete medial meniscectomy was carried to induce moderate to severe OA conditions to explore the efficacy of haMPCs, although ACLT alone was investigated in other rabbit moderate OA models [ 35 , 36 , 37 ]. We found that eroded cartilage was almost completely covered by the repaired tissues, and the hyaline cartilage specific marker, collagen II expression was increased in haMPC treatment group compared with HA group.…”
Section: Discussionmentioning
confidence: 99%
“…There are contradictory data regarding hypertrophic chondrocyte in OA. Some publications have indicated that terminal differentiation of chondrocytes into hypertrophy is associated with OA [ 6 , 43 , 44 ]. Therefore hypertrophy chondrocyte is considered as one of the hallmarks in OA.…”
Section: Discussionmentioning
confidence: 99%